EDUCATING MORAL QUALITIES IN PRIMARY SCHOOL STUDENTS, STRATEGIES AND RESULTS - Jalaldinova Madinakhan Khojakanovna (Galaxy International Interdisciplinary Research Journal, 2024)
Formation of moral qualities in elementary school students is an important aspect of their comprehensive development. This research paper examines the importance of instilling moral values in young students and examines effective strategies for instilling empathy, honesty, respect, and responsibility in elementary school. This article highlights the role of pedagogues, parents and the school community in the formation of students’ moral qualities, and shows the long-term impact of moral education on the social, emotional and academic well-being of students.